Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Dan Kepuasan Pelanggan Melalui Kualitas Pelayanan - Minta Kasih Hulu (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to analyze in depth marketing strategies in increasing sales and customer satisfaction through improving service quality amid increasingly intense and dynamic business competition. In a highly competitive market environment, companies are required to design and implement marketing strategies that not only focus on achieving short-term sales targets but also emphasize the creation of long-term value for customers. Therefore, an effective and customer-oriented marketing strategy becomes a crucial factor in maintaining business sustainability. The research employs a qualitative approach, with data collection techniques including in-depth interviews, direct observation, and documentation. This approach was chosen to obtain a comprehensive understanding of how marketing strategies are implemented, how service quality is perceived by customers, and what factors influence customer satisfaction and loyalty. By exploring these aspects in depth, the study seeks to reveal the interrelationship between marketing strategy, service quality, and customer behavior. The findings indicate that the success of marketing strategies is strongly influenced by the alignment of the marketing mix, which consists of product, price, place, and promotion. Competitive pricing that is proportional to product quality plays a significant role in attracting customer interest. In addition, consistent product quality and the selection of a strategic business location further strengthen the company’s position in the market. The utilization of digital technology, such as social media and online marketing platforms, has also proven effective in expanding market reach, enhancing communication with customers, and strengthening the company’s brand image.On the other hand, service quality plays a very significant role in shaping customer satisfaction. The dimensions of service quality, including reliability, responsiveness, assurance, empathy, and tangibles, have a strong influence on customers’ perceptions of the company. Fast, friendly, and professional service is able to create positive customer experiences, thereby increasing customer satisfaction levels. High customer satisfaction ultimately encourages repeat purchases and fosters customer loyalty. Therefore, it can be concluded that the harmonious integration of effective marketing strategies, superior service quality, and continuous innovation is a key factor in increasing sales and creating sustainable competitive advantage in an increasingly competitive business environment.